Poverty and Conditional Transfers: a Valuation Perspective from Medellín Solidaria’s Program - Muñetón Santa, Guberney; Bedoya Marulanda, John Fredy; Valencia Amaya, Mauricio Giovanni; Vanegas López, Juan Gabriel (Sociedad y Economía, 2013)
This paper seeks to identify the market prices of the different programs to which familiesbelonging to the governmental program “Medellín Solidaria” have accessed.Throughthe methodologies of replacement value and opportunity cost, the study measures thedirect value of 141 institutional programs, as well as the information-access cost of thegoods and services provided. The results show that the median annual value of the goodsand services accessed by the families is COP $507,678, but including the access to information,this figure raises to COP $650,000 annually. According to the results, an averagehousehold would be saving up to 13% of its annual income (at 2011 prices) thanks to itsaccess to Medellín Solidaria.